2018
DOI: 10.15516/cje.v20i3.2617
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Artistically Gifted Children in Visual Arts Teaching/Identifikacija likovno nadarene djece u nastavi likovne kulture

Abstract: The aim of this research was to evaluate how teachers recognize younger pupils who are artistically gifted (in visual arts). The participants were 150 elementary school teachers (1 st to 4 th grade) from the Split-Dalmatia County and the Dubrovnik-Neretva County in Croatia. Their task was to answer the questions in the two-part questionnaire in a truthful manner. The results showed that the participants were familiar with the characteristics by which they could recognize gifted children. There were also confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Comparing this research with the other of this kind we can generally conclude that teachers know what are the factors of artistic talent through which they can identify artistically gifted children. However, when observing the work of art itself, as was the case in the research conducted by Duh and Lep (2008) and, Brajcic and Kuscevic (2020), they fail to identify an artistically gifted student.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Comparing this research with the other of this kind we can generally conclude that teachers know what are the factors of artistic talent through which they can identify artistically gifted children. However, when observing the work of art itself, as was the case in the research conducted by Duh and Lep (2008) and, Brajcic and Kuscevic (2020), they fail to identify an artistically gifted student.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research that assessed teachers' ability to recognize artistic talent, using qualitative methods (Duh & Lep, 2008;Brajcic & Kuscevic, 2020) showed a very low level of ability to recognize artistically gifted children by teachers and educators.. Research conducted in Slovenia (Duh˛& Lep, 2008) and research conducted in Croatia (Brajcic & Kuscevic, 2020) showed that only 10% of teachers and educators are able to identify artistically gifted children. In the mentioned researched teachers and educators were offered art works of children for judgment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation